Promotive Efforts through Health Education about Toilet Training based on Iposyandu Parents - Hazairin, Ajeng Maulani; Susanti, Ari Indra; Didah, Didah (Universitas Padjadjaran, 2025)
According to WHO data in 2016, the incidence of skin irritation (diaper rash) was 25% out of 1,000,000 outpatient visits by infants. In Indonesia, the incidence of diaper rash based on data from the Ministry of Health’s Center for Data and Information in 2019 reached 7–35% of 23,604,923 children under the age of three, with 87,601 cases reported in Purwakarta Regency alone. This indicates that the prevalence of diaper rash remains high, primarily due to prolonged diaper use and parents’ lack of knowledge about signs of toilet training readiness, which often results in delays in its implementation. Delayed toilet training can negatively impact a child’s independence, making it important to provide health education for parents to help prevent long-term effects such as hindered self-reliance in children. This study aims to analyze the effect of health education on children's toilet training, delivered through the iPosyandu parent-based application, on mothers' knowledge and attitudes.The research employed a quantitative method using a one-group pretest-posttest design, involving 73 mothers of toddlers in Pasawahan Village, Purwakarta Regency. Samples meeting the inclusion criteria were selected using purposive sampling. Data were analyzed using the Wilcoxon signed-rank test and effect size value. The results showed significant differences in mothers’ knowledge and attitudes about children's toilet training before and after the health education intervention via the iPosyandu parent-based application (p < 0.05). Additionally, a strong influence was found between the educational intervention and improvements in both knowledge and attitudes (R ≥ 0.5). In conclusion, health education on children's toilet training delivered through the iPosyandu parent-based application significantly affects mothers’ knowledge and attitudes. Keywords: Attitude, health education, iPosyandu, knowledge, toilet training